Comparative performance analysis of cooperative and multi dual‐hop relay networks using MGF approach. (30th July 2020) - Asshad, Muhammad; Kavak, Adnan; Küçük, Kerem; Ahmad Khan, Sajjad
Summary: In this paper, we analyzed and compared the performance of cooperative diversity systems such as cooperative and multi dual‐hop networks with non‐regenerative relay nodes. The contributions of this study are twofolds. Firstly, analytical expressions of outage probability P o u t and average symbol error rate ASER are derived using moment generating function (MGF) analysis of the received SNR with the assumption that the channel experiences Weibull fading and the best relay selection is used. Then, using the analytical results, comparative performance evaluation of cooperative and multi dual‐hop relay networks is done for varying number of relay nodes and different receive diversity schemes such as maximal ratio combining (MRC) and selection combining (SC). The results show that the cooperative relay network has better performance than a multi dual‐hop relay network in terms of P o u t and ASER. The results also show that the multi dual‐hop network can achieve the same performance as the cooperative network with the requirement that it needs the deployment of three times more relay nodes. Abstract : In this study, we analyze the performance of cooperative diversity systems such as cooperative relay (Figure 1) and multi dual‐hop relay networks (Figure 2) by assuming non‐regenerative relay nodes in the network.